Dental bleaching with a 10% hydrogen peroxide product: a six-month clinical observation - Sundfeld, Renato Herman [UNESP]; Sundfeld Neto, Daniel [UNESP]; Machado, Lucas Silveira [UNESP]; Oliveira, Fernanda Garcia de [UNESP]; Alexandre, Rodrigo Sversut de [UNESP]; Palo, Renato Mioto [UNESP]; Sundfeld, Maria Lúcia M. M. [UNESP] (Wolters Kluwer, 2014)
Context: The possibility of bleaching vital teeth with peroxide-based products considerably revolutionized esthetic dentistry. Aim: The aim of this clinical study was to evaluate tooth color change and dental sensitivity after exposure to preloaded film containing a 10% hydrogen peroxide whitening system (Opalescence Trθswhite Supreme). Materials and Methods: A total of 13 volunteers, aged 18 to 25 years, participated in this study. The patients used the whitening system once a day for 60 minutes during the 8-day study. For maxillary incisors and canines, the color change was visually evaluated with the Vita color scale before, immediately, and six months after the treatment. Tooth sensitivity was evaluated during the daily gel applications. All whitening applications were done in office and under the supervision of a dental professional. Statistical Analysis Used: The results were analyzed using the Friedman Test (nonparametric repeated measures ANOVA) at a level of 5%, and Dunn's Multiple Comparison Test at the level of 5%. Results: It was verified that the original mean color values observed at the baseline analysis differed significantly from those observed immediately after bleaching, as well as from those seen in the analysis at six months ( P = 0.001). There was no significant difference between the mean color values observed in the immediate time and in the analysis at six months ( P = 0.474). No tooth sensitivity was observed in any patients. Conclusion: It was concluded that the bleaching technique using the 10% hydrogen peroxide system was effective in a short period of time without tooth sensitivity during applications.
Keywords: Clinical trial; Dentin hypersensitivity; Hydrogen peroxide; Tooth bleaching